Calcium Modulation, Anti-Oxidant and Anti-Inflammatory Effect of Skin Allergens Targeting the Nrf2 Signaling Pathway in Alzheimer's Disease Cellular Models - Silva, Ana (2020)
Experimental evidence highlights nuclear factor (erythroid-derived 2)-like 2 (Nrf2) as a molecular target in Alzheimer's disease (AD). The well-known effect of electrophilic cysteine-reactive skin allergens on Nrf2-activation led to the hypothesis that these compounds could have a therapeutic role in AD. This was further supported by the neuroprotective activity of the skin allergen dimethyl fumarate (DMF), demonstrated in in vivo models of neurodegenerative diseases. We evaluated the effect of the cysteine-reactive allergens 1,4-phenylenediamine (PPD) and methyl heptine carbonate (MHC) on (1) neuronal redox imbalance and calcium dyshomeostasis using N2a wild-type (N2a-wt) and human APP-overexpressing neuronal cells (wild-type, N2a-APPwt) and (2) on neuroinflammation, using microglia BV-2 cells exposed to LPS (lipopolysaccharide). Phthalic anhydride (PA, mainly lysine-reactive), was used as a negative control. DMF, PPD and MHC increased Hmox1 gene and HMOX1 protein levels in N2a-APPwt cells suggesting Nrf2-dependent antioxidant activity. MHC, but also PA, rescued N2a-APPwt mitochondrial membrane potential and calcium levels in a Nrf2-independent pathway. All the chemicals showed anti-inflammatory activity by decreasing iNOS protein in microglia. This work highlights the potential neuroprotective and anti-inflammatory role of the selected skin allergens in in vitro models of AD, and supports further studies envisaging the validation of the results using in vivo AD models.